Racial and weight discrimination associations with pain intensity and pain interference in an ethnically diverse sample of adults with obesity: a baseline analysis of the clustered randomized-controlled clinical trial the goals for eating and moving (GEM) study - Ericka N. Merriwether; Sandra Wittleder; Gawon Cho; Eushavia Bogan; Rachel Thomas; Naja Bostwick; Binhuan Wang; Joseph Ravenell; Melanie Jay (BMC, 2021)
Abstract Background Everyday experiences with racial (RD) and weight discrimination (WD) are risk factors for chronic pain in ethnically diverse adults with obesity. However, the individual or combined effects of RD and WD on pain in adults with obesity is not well understood. There are gender differences and sexual dimorphisms in nociception and pain, but the effect of gender on relationships between RD, WD, and pain outcomes in ethnically diverse adults with obesity is unclear. Thus, the purposes of this study were to: 1) examine whether RD and WD are associated with pain intensity and interference, and 2) explore gender as a moderator of the associations between RD, WD, and pain. Methods This is a baseline data analysis from a randomized, controlled clinical trial of a lifestyle weight-management intervention. Eligible participants were English or Spanish-speaking (ages 18-69 years) and had either a body mass index of ≥30 kg/m2 or ≥ 25 kg/m2 with weight-related comorbidity. RD and WD were measured using questions derived from the Experiences of Discrimination questionnaire (EOD). Pain interference and intensity were measured using the PROMIS 29 adult profile V2.1. Linear regression models were performed to determine the associations between WD, RD, gender, and pain outcomes. Results Participants (n = 483) reported mild pain interference (T-score: 52.65 ± 10.29) and moderate pain intensity (4.23 ± 3.15). RD was more strongly associated with pain interference in women (b = .47, SE = .08, p < 001), compared to men (b = .14, SE = .07, p = .06). Also, there were no significant interaction effects between RD and gender on pain intensity, or between WD and gender on pain interference or pain intensity. Conclusions Pain is highly prevalent in adults with obesity, and is impacted by the frequencies of experiences with RD and WD. Further, discrimination against adults with obesity and chronic pain could exacerbate existing racial disparities in pain and weight management. Asking ethnically diverse adults with obesity about their pain and their experiences of RD and WD could help clinicians make culturally informed assessment and intervention decisions that address barriers to pain relief and weight loss. Trial registration NCT03006328